Variability of 18S rDNA locus among Symphysodon fishes: chromosomal rearrangements - Gross, M. C.; Schneider, C. H.; Valente, G. T. [UNESP]; Martins, C. [UNESP]; Feldberg, E. (Wiley-Blackwell, 2010)
Three species of cichlids belonging to the genus Symphysodon have demonstrated interspecific and intraspecific variation in nucleolus organizer regions (NOR) detected with silver nitrate. In order to understand the evolution of this marker in the genus, the structural variability of these sequences in mitotic chromosomes from Symphysodon aequifasciatus, Symphysodon discus and Symphysodon haraldi was investigated using both silver nitrate impregnation and hybridization of the 18S rRNA gene probe. For the three species, the two markers were intraspecifically and interspecifically variable both in the number and in the size of the sites. This polymorphism may stem from duplications and translocations, which suggests that structural chromosome rearrangements effectively act in the karyoevolution of wild Symphysodon species and may have favoured the adaptability of these fishes to diverse aquatic environments in the Amazon.
Keywords: Amazon basin; chromosome evolution; discus fish; fluorescent in situ hybridization; Symphysodon spp